EFL Lecturers’ Challenges and Suggestions in the Online Teaching - Mukminatus Zuhriyah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
Online EFL teaching and learning in universities has been conducted for two years during the COVID-19 pandemic. However, the EFL lecturers’ challenges in small private universities in Indonesia are still scarcely investigated. Therefore, this research was conducted with the purpose to describe the Indonesian EFL lecturers’ challenges in their online teaching in the small private universities where they teach English. This was a qualitative research which used online semi-structured interview to six EFL lecturers from six different private universities in East Java to collect the data. Meanwhile, those six private universities did not have the official online platform for online teaching yet. The theory of Miles, Huberman, and Saldana was used to analyze the data. The result was that they faced some challenges in their online EFL teaching related to their students’ presence, the bad internet connection, the unconducive home condition, and the very slow students’ responses. Besides, they suggested to the universities to provide the official online learning platform which is completed with the places for storing their teaching administration archives. Hopefully, these research results can be the consideration for the university policy makers when deciding the guidelines of the online teaching and learning in the universities.